Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/met6070148
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of AlSi10Mg Alloy Produced by Additive Manufacturing (AM) vs. Its Counterpart Gravity Cast Alloy

Abstract: Abstract:The attractiveness of additive manufacturing (AM) relates to the ability of this technology to rapidly produce very complex components at affordable costs. However, the properties and corrosion behavior, in particular, of products produced by AM technology should at least match the properties obtained by conventional technologies. The present study aims at evaluating the corrosion behavior and corrosion fatigue endurance of AlSi10Mg alloy produced by selective laser melting (SLM) in comparison with it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 22 publications
5
46
0
Order By: Relevance
“…Yet, studies published over the last few months have started to bring new insights in that respect. Leon et al have compared the corrosion resistance of LBM AlSi10Mg with gravity cast A360.2 of a very similar chemical composition. They found that LBM AlSi10Mg exhibited slightly reduced corrosion rates in a 3.5% NaCl solution in comparison with its cast counterpart.…”
Section: Am Of Al Alloyssupporting
confidence: 61%
“…Yet, studies published over the last few months have started to bring new insights in that respect. Leon et al have compared the corrosion resistance of LBM AlSi10Mg with gravity cast A360.2 of a very similar chemical composition. They found that LBM AlSi10Mg exhibited slightly reduced corrosion rates in a 3.5% NaCl solution in comparison with its cast counterpart.…”
Section: Am Of Al Alloyssupporting
confidence: 61%
“…Aboulkhair et al have investigated the effect of a conventional T6 heat treatment, and observed a significant spatial variation within the tested region and little benefit in properties (Table ). Corrosion resistance can be slightly improved by the SLM process compared to its counterpart gravity cast alloy …”
Section: Alloy Development For Metal Ammentioning
confidence: 99%
“…The growing interest in additive manufacturing (AM) technology in the last decade has been largely due to the inherent advantages of this technology in terms of creating highly complex geometries in a relatively short time [1][2][3][4][5][6]. Currently, most relevant production and research activities focus on 3D printing processes using powder bed technology (PBT), such as selective laser melting (SLM) and electron beam melting (EBM) [7].…”
Section: Introductionmentioning
confidence: 99%